Flexoelectric Domain Walls Originated from Structural Phase Transition in Epitaxial BiVO4 Films. Issue 19 (24th March 2022) - Shao, Pao‐Wen; Liu, Heng‐Jui; Sun, Yuanwei; Wu, Mei; Peng, Ren‐Ci; Wang, Meng; Xue, Fei; Cheng, Xiaoxing; Su, Lei; Gao, Peng; Yu, Pu; Chen, Long‐Qing; et al.
Abstract: Polar domain walls in centrosymmetric ferroelastics induce inhomogeneity that is the origin of advantageous multifunctionality. In particular, polar domain walls promote charge‐carrier separation and hence are promising for energy conversion applications that overcome the hurdles of the rate‐limiting step in the traditional photoelectrochemical water splitting processes. Yet, while macroscopic studies investigate the materials at the device scale, the origin of this phenomenon in general and the emergence of polar domain walls during the structural phase transition in particular has remained elusive, encumbering the development of this attractive system. Here, it is demonstrated that twin domain walls arise in centrosymmetric BiVO4 films and they exhibit localized piezoelectricity. It is also shown that during the structural phase transition from the tetragonal to monoclinic, the symmetry reduction is accompanied by an emergence of strain gradient, giving rise to flexoelectric effect and the polar domain walls. These results not only expose the emergence of polar domain walls at centrosymmetric systems by means of direct observation, but they also expand the realm of potential application of ferroelastics, especially in photoelectrochemistry and local piezoelectricity. Abstract : The current bottleneck of realizing the origin and mechanism of polar domain walls in centrosymmetric materials is the straight evidence between residual strain and polar domain walls since the residual strain would be released in the defect‐rich area. In this study, epitaxial centrosymmetric BiVO4 films with twin domains are investigated, while polar domain walls arise from flexoelectricity by spontaneous strain gradient.